Peranan BSPS Terhadap Ekonomi dan Sosial Penerima Bantuan di Kecamatan Simpang Empat - Khairunnisa; Nasruddin (PPJP ULM, 2019)
This study aims to determine the role of self-help housing stimulant programs foreconomic and social on economic and social assistance recipients in Simpang Empat District.The research respondents were 42 beneficiaries with data collection techniques throughquestionnaires, observation, and documentation. The data analysis techniques used aredescriptive analysis, which is the presentation of data in tabulation form which computes thepercentage for each answer category and is processed on research needs, which are theninterpreted according to findings in the field.This research of self-help housing stimulant programs is playing a role in the economyby providing jobs for builders. The social conditions of beneficiaries play a role in improvingcomfort and safety, health, and improving housing conditions. In contrast, the economy ofbeneficiaries has not changed.